UNCOVERING THE EFFECTS OF E-LEADERSHIP PERCEPTION ON EMPLOYEE ADAPTATION AND PRODUCTIVITY IN INDONESIAN STARTUP ORGANIZATIONS - Yogatama, Ahmad Nizar; Anjaningrum, Widiya Dewi (Program Sarjana Manajemen Universitas Internasional Batam, 2024)
The objective of this research was to examine the relationships between various variables in the context of startup companies in Indonesia. The study was conducted over the course of one academic year, specifically 2022/2023, within a startup company in Indonesia. A sample of 270 respondents was randomly selected from the target population. Partial least squares structural equation modeling (PLS-SEM) was employed as the analytical technique. The t-test results indicated a positive influence of perceived e-leadership on teleworking output, subsequently impacting employee adaptive performance. Furthermore, transparent communication had a significant positive direct effect on employee adaptive performance, with a path coefficient of 0.286 (positive) and a p-value of 0.001-0.005 (significant). These findings highlight the importance of transparent communication in enhancing employee adaptive performance. The results have practical implications for decision-making processes and can potentially contribute to the development of effective strategies and practices within the industry.